Germany versus the United States: Monetary Dominance in the Eurozone - Chee-Heong Quah (Economies, 2016)
This study inspects if there is greater convergence with Germany amongst the Eurozone founding members and if their relations with the hegemonic economy have been more symmetrical after "euroization". The dimensions explored are those inspired by the optimum currency areas (OCA) framework. To some extent, the findings could signify if real convergence has been significantly endogenous. At the same time, to assess the relative dominance of Germany, the features against Germany are compared to those against US. In addition, the paper also appraises some aspects of economic performance to check whether economic conditions across the states have improved and converged after unification. In some convergence aspects, findings suggest remarkable convergence with Germany and across the states but also relative convergence with US. On economic erformance, results indicate substantial improvements in inflation and unemployment. Amongst the founding states, Ireland has idiosyncratically shown serious divergences in a number of the convergence and performance measures.
Keywords: E62; F31; F32; F41; F42; O53; 330; EMU; optimum currency area; Euro; debt; Germany; exchange rate; money; currency; US